1997
DOI: 10.1111/jon1997718
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Differential Diagnosis of Nontumor Central Nervous System Diseases from Tumors

Abstract: To accurately differentiate nontumor central nervous system (CNS) diseases from brain tumors, we retrospectively evaluated the cerebral circulation and metabolism in patients with nontumor CNS diseases using positron emission tomography (PET). Regional cerebral blood flow (rCBF), cerebral blood volume (rCBV), oxygen extraction fraction (rOEF), the metabolic rates of oxygen (rCMRO2), and of glucose (rCMRGI), and the uptake of 11C-methyl-L-methionine (11C-Met) were visually evaluated in lesions and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…This is in contrast to other experimental studies that reported uptake of 14 C-MET predominantly in viable tumor cells, with low uptake in macrophages and other cells (21). Our observations, however, are in line with case reports and studies on small patient groups that have shown accumulation of 11 C-MET in brain abscesses (22)(23)(24).…”
Section: Discussionsupporting
confidence: 92%
“…This is in contrast to other experimental studies that reported uptake of 14 C-MET predominantly in viable tumor cells, with low uptake in macrophages and other cells (21). Our observations, however, are in line with case reports and studies on small patient groups that have shown accumulation of 11 C-MET in brain abscesses (22)(23)(24).…”
Section: Discussionsupporting
confidence: 92%
“…We experienced several cases with radiation necrosis which had high accumulation of 11 Cmethionine. There have been some reports of radiation necrosis with 11 C-methionine accumulation, and the reason is considered to be inflammatory change, reactive gliosis or blood-brain barrier disruption [11,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In general, MET uptake is lower in low-grade than in high-grade gliomas, although there is considerable overlap between these two groups, as well as between histological types [4,5]. However, several previous reports have demonstrated MET uptake in lesions associated with benign brain diseases [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Although Ito et al [6] have already reported on the imaging spectrum and pitfalls of MET-PET/CT in intracranial lesions, in this review we focus on and introduce imaging characteristics of MET uptake in benign brain disease through a literature review.…”
mentioning
confidence: 83%
“…High MET uptake has also been reported with cerebrovascular diseases (CVDs) such as cerebral infarction [8][9][10][11]. Nakagawa, et al [8] reported that the mean MET uptake in cerebral infarctions was 1.07 卤 0.28 (range 0.67-1.31) the TNR, with this value depending on the day of onset.…”
Section: Cerebral Infarctionmentioning
confidence: 99%